Cost-effectiveness of imaging strategies to diagnose and select patients with non-obstructive coronary artery disease for statin treatment in the United Kingdom. (8th February 2021) - Peultier, A; Redekop, WK; Boccalini, S; Clayton, B; Severens, JL
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): The project leading to this publication has received funding from the European Union's Horizon 2020 research and innovation programme under grant agreement No 668142. Background: Patients with non-obstructive coronary artery disease (NOCAD) are at a higher risk of cardiovascular events compared to those with normal arteries. Plaque rupture is associated with increased adverse events and statin therapy seems to be beneficial for plaque stabilisation. Coronary Computed Tomography Angiography (CCTA) is currently the non-invasive imaging modality of choice for the morphological evaluation of NOCAD in the United Kingdom (UK). However, CCTA provides limited information regarding the vulnerability of plaques to rupture and the selection of patients for preventive statin treatment. Currently being tested on patients, Spectral Photon-Counting CT (SPCCT) may provide increased accuracy for vulnerable plaque detection and, in turn, improved selection of patients for statin treatment. Purpose: We investigated the potential cost-effectiveness of SPCCT (compared to a set of CCTA-based strategies) in identifying NOCAD patients with rupture-prone plaques for preventive statin treatment. Methods: A decision tree and a Markov trace were developed to model the expected outcomes (costs and quality-adjusted life-years (QALYs)) for a hypothetical UK cohort of 50-year-old male patients with stable chest pain and no history of CAD. Input data were obtained from the literature. Deterministic and probabilistic sensitivity analyses were performed. The impact of a pairwise variation of SPCCT sensitivity and specificity was analysed. Furthermore, five competing imaging strategies were compared in terms of their lifetime costs and effects: 1) CCTA and treat NOCAD based on imaging results, 2) CCTA and treat all NOCAD, 3) CCTA and do not treat NOCAD, 4) SPCCT with high specificity and treat NOCAD based on imaging results, and 5) SPCCT with high sensitivity and treat NOCAD based on imaging results. Results: Our deterministic and probabilistic results showed that an improved imaging test would add value compared to CCTA. While increased specificity (to 95%) is favorable at a lower willingness to pay (WTP) (up to ∼£9, 000 per QALY), increased sensitivity (to 95%) is more likely to be favorable at a higher WTP (∼£9, 000 to £120, 000 per QALY). The role of a CCTA-treat-none strategy and a CCTA-treat-all strategy is minimal and potential only at really low (<£2, 000 per QALY) and high (>£120, 000 per QALY) WTP, respectively. The uncertainty around these results is highly correlated to the uncertainty around the long-term risk for NOCAD patients to experience myocardial infarction or stroke. Conclusion: An improved imaging test based on higher sensitivity in identifying rupture-prone coronary plaques in NOCAD patients seems to have value in guiding the decision of preventive statin treatment in the UK. However, additional data regarding the efficacy of statins and of combined treatments for NOCAD patients are needed before the cost-effectiveness of SPCCT can be precisely estimated in this population.